ASSISTANCE IN THE PREPARATION OF FINANCIAL REPORTS AT THE "LESTARI MANDIRI" MICROFINANCE INSTITUTION RAGUKLAMPITAN JEPARA - Hazmi, Faiqul; R. Musfiroh, Mayadina; Fauzan Mubarok, Ahmad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
This service activity assists the microfinance institution Lestari Mandiri Raguklampitan Batealit Jepara. The activities of Lestari Mandiri microfinance service partners include providing savings and loan services to their members independently and visitors. The organization is owned, managed, and utilized independently by the community in the local village. The purpose of the service is to increase knowledge in terms of recording and making financial reports according to standards. The problems faced by partners are recording savings and loan transactions is still done manually so it requires accuracy and thoroughness from the manager so that it is less efficient. These things may be problems and risks in the form of data, data redundancy, and the difficulty of knowing financial information in the form of costs, income, and balance sheets, as well as difficulties in getting late and accurate payment data (2) This is the first point, causes another problem in the form of recording payments as well as the management of financing carried out by the manager. The solution provided is under business needs by (1) Providing training in financial reporting to comply with standards. (Providing training in financing management). This mentoring and training method is carried out with an in-house training approach, strengthening groups, and continuous mentoring. The results obtained are gaining new knowledge, Improving financing procedures, partners can make financial reports independently, and making it easier for partners to make decisions that are taken.